The image of the woman in AL_ AHWAS AL_ ANSARI'S poetry - أحمد, عدنان; حبيب, فاطمه (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research aims at studying the image of woman of one of the Omayyad poets, and sheds light on the features of the novelty and uniqueness that accompanied it at that epoch, and on the traditions that remained faithful to the ancestral heritage. This research examines the psychological dimensions of This image and it is relation to the life of The poet and it is distant meaning in his poetry. The image of woman was not a rigid description of certain aesthetic features but carried deeper meanings in the human psyche it was a symbol of life, fertility and wealth which the old man used to face the Cruelty of his reality and the cruelty his psyche .It revealed human insights and revealed the vision of the poet and his fears introduced his suffering, sensation, and his deepest fears in that epoch. The research shows the ability of the sensual image to reveal deeper meanings affecting the human psyche, the importance of the image in studying poetry and revealing the hidden aspects of the poem and the poets attitude to reality. It is the constant essence in poetry no matter how different its purposes, and it is the most important measure of the quality of creativity and skills the poet has, hence, using the artistic image, the poet presents his feelings, sensations thought and vision to the world